Phenotypical and functional profiles of natural killer cells exhibiting matrix metalloproteinase-mediated CD16 cleavage after anti-HIV antibody-dependent activation - Tang, C-C (Clin Exp Immunol, 2015)
Natural killer (NK) cell-mediated antibody-dependent cellular cytotoxicity (ADCC) has been linked to protection from HIV infection and slower progression towards AIDS. However, antibody-dependent activation of NK cells results in phenotypical alterations similar to those observed on NK cells from individuals with progressive HIV infection. Activation of NK cells induces matrix metalloproteinase (MMP)-mediated cleavage of cell surface CD16. In the present study we assessed the phenotype and functional profile of NK cells exhibiting post-activation MMP-mediated CD16 cleavage. We found that NK cells achieving the highest levels of activation during stimulation exhibit the most profound decreases in CD16 expression. Further, we observed that educated KIR3DL1(+) NK cells from human leucocyte antigen (HLA)-Bw4-carrying donors exhibit larger decreases in CD16 expression post-activation than the KIR3DL1(−) NK cell subset containing cells educated via other inhibitory receptor/ligand combinations and non-educated NK cells. Lastly, we assessed the ex-vivo expression of CD16 on educated KIR3DL1(+) NK cells and the KIR3DL1(−) NK cell subset from HLA-Bw4-carrying HIV-uninfected and HIV-infected donors. Suggestive of in-vivo activation of KIR3DL1(+) NK cells during HIV infection, CD16 expression was higher on KIR3DL1(+) than KIR3DL1(−) NK cells in uninfected donors but similar on both subsets in HIV-infected donors. These results are discussed in the context of how they may assist with understanding HIV disease progression and the design of immunotherapies that utilize antibody-dependent NK cell responses.